Griffithsin Inhibits Nipah Virus Entry and Fusion and Can Protect Syrian Golden Hamsters From Lethal Nipah Virus Challenge. (10th February 2020) - Lo, Michael K; Spengler, Jessica R; Krumpe, Lauren R H; Welch, Stephen R; Chattopadhyay, Anasuya; Harmon, Jessica R; Coleman-McCray, JoAnn D; Scholte, Florine E M; Hotard, Anne L; Fuqua, Joshua L; Rose, John K; Nichol, Stuart T; et al.
Abstract: Nipah virus (NiV) is a highly pathogenic zoonotic paramyxovirus that causes fatal encephalitis and respiratory disease in humans. There is currently no approved therapeutic for human use against NiV infection. Griffithsin (GRFT) is high-mannose oligosaccharide binding lectin that has shown in vivo broad-spectrum activity against viruses, including severe acute respiratory syndrome coronavirus, human immunodeficiency virus 1, hepatitis C virus, and Japanese encephalitis virus. In this study, we evaluated the in vitro antiviral activities of GRFT and its synthetic trimeric tandemer (3mG) against NiV and other viruses from 4 virus families. The 3mG had comparatively greater potency than GRFT against NiV due to its enhanced ability to block NiV glycoprotein-induced syncytia formation. Our initial in vivo prophylactic evaluation of an oxidation-resistant GRFT (Q-GRFT) showed significant protection against lethal NiV challenge in Syrian golden hamsters. Our results warrant further development of Q-GRFT and 3mG as potential NiV therapeutics.